A model for the initial diagnosis of cerebellar disease. (1st February 2017) - Chiba, Ryosuke; Shiraishi, Sho; Takakusaki, Kaoru; Ota, Jun
Abstract: Early diagnosis of potential cerebellar disease is incredibly important, as it allows rapid intervention and treatment of the identified disorder. More effective diagnosis and treatment would be aided by identification of which specific cerebellar regions are impaired. In this paper, we propose a method for initial diagnosis of regional cerebellar impairments. Our model uses motor functions as regional intermediaries for the outputs and various indexes (motor assessments) as the inputs. We also discuss which indexes indicate possible disordered functions. We tested our proposed method by applying it experimentally to the diagnosis of cerebellar disorder in rats. The percentage of correct estimations was 74.5%. We consider this a sufficiently high rate for initial diagnosis and suggest that it may be more effective when applied to humans. Abstract :